The Story of General Dann and Mara's Saughter, Griot and the Snow Dog : A Novel - Lessing, Doris (London Harper Perennial, 2006)
A fascinating novel of love and ecology from the winner of the Nobel Prize for Literature.
A Novel.
Keywords: Regression (Civilization) -- Climatic changes -- Storytellers